2016
DOI: 10.1371/journal.pone.0161721
|View full text |Cite
|
Sign up to set email alerts
|

Target Product Profile for a Diagnostic Assay to Differentiate between Bacterial and Non-Bacterial Infections and Reduce Antimicrobial Overuse in Resource-Limited Settings: An Expert Consensus

Abstract: Acute fever is one of the most common presenting symptoms globally. In order to reduce the empiric use of antimicrobial drugs and improve outcomes, it is essential to improve diagnostic capabilities. In the absence of microbiology facilities in low-income settings, an assay to distinguish bacterial from non-bacterial causes would be a critical first step. To ensure that patient and market needs are met, the requirements of such a test should be specified in a target product profile (TPP). To identify minimal/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 41 publications
1
105
1
2
Order By: Relevance
“…These models meet or exceed the performance guidelines proposed by a FIND-sponsored expert consensus document for a diagnostic test of bacterial pneumonia. 14 Because the BvV model was highly predictive, we investigated the underlying marker proteins for information about the inflammatory processes that typify bacterial and viral infections. Gene enrichment and pathway analyses showed that the processes in bacterial infections were dominated by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models meet or exceed the performance guidelines proposed by a FIND-sponsored expert consensus document for a diagnostic test of bacterial pneumonia. 14 Because the BvV model was highly predictive, we investigated the underlying marker proteins for information about the inflammatory processes that typify bacterial and viral infections. Gene enrichment and pathway analyses showed that the processes in bacterial infections were dominated by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, host response signatures have been explored as possible diagnostic indicators. To date, however, these approaches have not proven to be sufficiently reliable [9][10][11][12][13] , based on a recommended benchmark 14 of acceptable and desirable thresholds for sensitivity (desirable ≥95%, acceptable ≥90%) and specificity (≥90% and ≥80%) for diagnostic tests. We hypothesized that the distinctive cellular host responses could be detected at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…The ASSURED criteria, together with additional specific requirements, are summarized in Target Product Profiles (TPPs), which technology developers should meet during their development stages. Examples of TPPs exist for tuberculosis, Ebola, and differentiation between viral and bacterial infections, and are driven by the WHO, the Médecins Sans Frontières (MSF), the Foundation for Innovative New Diagnostics (FIND), and other organizations [36,37].…”
Section: Target Groups and End-user Requirementsmentioning
confidence: 99%
“…Healthcare-or community-associated invasive bacterial infection Gram stain, where expertise exists; however not of use for bloodstream infections and prone to many errors [12] Bacterial culture and antimicrobial susceptibility testing [12,19] Implementation of quality-assured basic techniques is lacking in most LRS reference laboratories and should be prioritized [12,19] At the primary level: biomarker and digitally assisted decision tools to distinguish bacterial from non-bacterial fevers [8] and/or multi-disease detection platforms [64] At the secondary levelþ: simplified approaches to classic bacteriology techniques [12], new tools for rapid phenotypic determination of AST NAAT and MALDI-TOF-based AST face significant challenges because of the wide array and changeability of mechanisms of resistance Dengue…”
Section: Current Diagnostic Gaps And/or Innovations Required Bmentioning
confidence: 99%
“…Combination RDTs that detect both IgM/IgG and the NS1 antigen [65]. Able to diagnose dengue at different points in time after initiation of symptoms Commercial availability and production history of RDT has been inconsistent since its introduction At the primary level: biomarker and digitally assisted decision tools to distinguish bacterial from non-bacterial fevers [8] and/or multi-disease detection platforms [64] At the secondary levelþ: simplified approaches to classic bacteriology techniques [12,50] resource settings may play in the near future, and how they can interact with end-users and NMFI patients ( Fig. 1).…”
Section: Current Diagnostic Gaps And/or Innovations Required Bmentioning
confidence: 99%